TRANSMIGRATIONS IN THE UPANISHADS AND THE GREEK THOUGHT: . - Aranjaniyil, Gabriel (Journal of Dharma, 2002)
Transmigration is a belief taken for granted in Hinduism, Buddhism and Jainism. It was during the Upanishads period that this belief became prevalent in India. The Upanishads, during the formation of which Buddhism and Jainisrn arose as a reaction to Brahmanic Hinduism, first taught this doctrine. Among the Greeks, it was Plato who gave a significant role to this theory in his philosophy. His philosophy is close to the Upanishadic view in many ways. He wrote his dialogues when the later Upanishads were taking shape. This article is an attempt to study the Upanishadic and Platonic views of Transmigration.